Three amino acid residues bind corn odorants to McinOBP1 in the polyembryonic endoparasitoid of Macrocentrus cingulum Brischke. - Tofael Ahmed; Tian-tao Zhang; Zhen-ying Wang; Kang-lai He; Shu-xiong Bai (PLoS ONE)
Odorant binding proteins (OBPs) play a central role in transporting odorant molecules from the sensillum lymph to olfactory receptors to initiate behavioral responses. In this study, the OBP of Macrocentrus cingulum McinOBP1 was expressed in Escherichia coli and purified by Ni ion affinity chromatography. Real-time PCR experiments indicate that the McinOBP1 is expressed mainly in adult antennae, with expression levels differing by sex. Ligand-binding experiments using N-phenyl-naphthylamine (1-NPN) as a fluorescent probe demonstrated that the McinOBP1 can bind green-leaf volatiles, including aldehydes and terpenoids, but also can bind aliphatic alcohols with good affinity, in the order trans-2-nonenal>cis-3-hexen-1-ol>trans-caryophelle, suggesting a role of McinOBP1 in general odorant chemoreception. We chose those three odorants for further homology modeling and ligand docking based on their binding affinity. The Val58, Leu62 and Glu130 are the key amino acids in the binding pockets that bind with these three odorants. The three mutants, Val58, Leu62 and Glu130, where the valine, leucine and glutamic residues were replaced by alanine, proline and alanine, respectively; showed reduced affinity to these odorants. This information suggests, Val58, Leu62 and Glu130 are involved in the binding of these compounds, possibly through the specific recognition of ligands that forms hydrogen bonds with the ligands functional groups.